Total productive maintenance implementation’s barriers and enablers in Indonesian manufacturing companies - Prabowo, Herry Agung; Hilmy, Irfan; Adesta, Erry Yulian Triblas (Institute of Electrical and Electronics Engineers Inc., 2020)
Nowadays, Corporate is implementing Total Productive Maintenance (TPM) in order to survive in a very challenging and competitive market. If they want to survive, the have to maintain and even increase their equipment efficiency. However, the TPM utilization is a relatively difficult activity. Some obstacles as well as the supporting factors will determine the speed of the implementation process. Identifying and analyzing those obstacles and supporting factor are very important steps to gain an effective utilization of the TPM. The main discussion of this research is to acquire the significant barriers and enablers of TPM implementation in Indonesian manufacturing companies using Cochran test analysis. In this report, these barriers and enablers have been determined through the literature; data collecting is done by a questionnaire-based survey. There are five significant enablers and seven barriers affecting the achievement rate of TPM.